2019
DOI: 10.1186/s13244-019-0747-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation in the ankle and foot: from incidental finding to inductor of pathology. Part II: midfooot and forefoot

Abstract: Accessory anatomical structures in the ankle and foot usually represent incidental imaging findings; however, they may also eventually represent a source of pathology, such as painful syndromes, degenerative changes, be the subject of overuse and trauma, or appear as masses and cause compression syndromes or impingement. This review aims to describe and illustrate the imaging findings related to the presence of accessory ossicles and muscles in the midfoot and forefoot through different techniques, with specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
1
17
2
Order By: Relevance
“…[4,6,8] The reported prevalence in literature is between 4 and 21%. [3] Our study results show prevalence is 13.06% {Table 2}, which is in the range of reported prevalence in the literature. East et al estimated prevalence is 5.8%, and the frequency is higher in females than males.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…[4,6,8] The reported prevalence in literature is between 4 and 21%. [3] Our study results show prevalence is 13.06% {Table 2}, which is in the range of reported prevalence in the literature. East et al estimated prevalence is 5.8%, and the frequency is higher in females than males.…”
Section: Discussionsupporting
confidence: 65%
“…[4,5] Usually, asymptomatic, serious associated pathology is irreducible dislocated IP joint due to its interposition. [3,4] Nigar et al reported prevalence of interphalangeal joint sesamoid was ~ 2% [5%]. Our study shows a 5.2 % {Table 1, Figure 1 (f)}, prevalence higher than the reported prevalence in Nigar study done in Turkish subjects.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations